Predicting dropout in male youth soccer using the theory of planned behavior - Nache, C. M.; Bar-Eli, M.; Perrin, C.; Laurencelle, L. (Scandinavian Journal of Medicine & Science in Sports, 2005)
This investigation prospectively predicted dropout among young soccer players, using the theory of planned behavior (TPB). First, behavioral beliefs required to develop a TPB-questionnaire were elicited from 53 male soccer players, aged 1315 years. Second, at the beginning of the soccer season, 354 different male soccer players aged 1315 years completed this questionnaire, thereby assessing direct dimensions (intention, attitude, subjective norm, perceived control) and indirect dimensions (attitudinal, normative and control beliefs) derived from TPB. Nine months later upon termination of the soccer season these players were classified into 323 perserverers and 31 dropouts, with TPB being applied prospectively to predict these two groups. For both direct and indirect dimensions, between-group comparisons revealed significant differences in favor of the perseverers. Discriminant analyses revealed five measures (intention, attitude, subjective norm, a normative belief, and a control belief), which enabled a 22.1% a priori dropout prediction when used within a suitable equation. In conclusion, TPB may have a promising application to prospectively discriminate dropouts from perseverers, providing a potential predictive a priori classification model for sport participation.